Direct reciprocity stabilizes simultaneous hermaphroditism at high mating rates: A model of sex allocation with egg trading. (1st August 2015) - Henshaw, Jonathan M.; Kokko, Hanna; Jennions, Michael D.
Abstract: Simultaneous hermaphroditism is predicted to be unstable at high mating rates given an associated increase in sperm competition. The existence of reciprocal egg trading, which requires both hermaphroditism and high mating rates to evolve, is consequently hard to explain. We show using mathematical models that the presence of a trading economy creates an additional fitness benefit to egg production, which selects for traders to bias their sex allocation toward the female function. This female‐biased sex allocation prevents pure females from invading a trading population, thereby allowing simultaneous hermaphroditism to persist stably at much higher levels of sperm competition than would otherwise be expected. More generally, our model highlights that simultaneous hermaphroditism can persist stably when mating opportunities are abundant, as long as sperm competition remains low. It also predicts that reciprocity will select for heavier investment in the traded resource.